Prediksi Kinetika Transpor Transdermal Propranolol HCl dengan Program WinSAAM - LUCIA HENDRIATI; AKHMAD KHARIS NUGROHO (JURNAL ILMU KEFARMASIAN INDONESIA, 2011)
Transdermal transport was an alternate to propranolol HCl delivery to overcome the low bioavailability by oral route. Kinetics of transdermal transport can be predicted by software WinSAAM. The aim of this research was to know kinetics of propranolol HCl transdermal transport with the present of enhancer oleic acid, propylene glycol and iontophoretics. Propranolol HCl transdermal transport was examined through the hairless rat as membrane on the vertical diffusion cell in the in vitro permeation. Enhancement methode used was oleic acid in propylene glycol and iontophoretics at varying concentrations. The donor phase contained 5 mg/mL propranolol HCl in citrate buffer, and the acceptor phase contained phosphate buffer saline at pH 7.4. Results of propranolol HCl transdermal transport analyzed by WinSAAM software. Parameters of transdermal transport were the rate of mass transfer from donor compartement to skin (Ka), available dose to transport (AD), and the rate of mass transfer from skin to acceptor compartement (KR).The results indicated that propranolol HCl transdermal transport with the present of enhancer can be explained by three compartement model and first order kinetics. Theoretically, value of AD influenced by oleic acid, interaction of oleic acid-iontophoretics and interaction of propylene glycol-iontophoretics. Value of Ka inliuenced by iontophoretics and interaction of oleic acid-propylene glycol-iontophoretics. Value of KR induenced by iontophoretics.